The Impact of Local Public Services and Geographical Cost of Living Differences on Poverty Estimates - Rolf Aaberge; Audun Langørgen; Magne Mogstad; Marit Østensen (Statistics Norway, Research Department, 2008)
Despite a broad consensus on the need to account for the value of public services and geographical cost of living differences on the measurement of poverty, there is little reliable evidence on how these factors actually affect poverty estimates. Unlike the standard approach in studies of the distribution of public services, this paper employs a method for valuing sector-specific local public services that accounts for differences between municipalities in the costs and capacity to produce public services. Furthermore, recipient frequencies in various demographic groups are used as the basis for determining the allocation of the value of these services on citizens of the municipalities. Geographical differences in living costs are accounted for by using municipal housing price indices or by replacing the country-specific poverty line with municipal-specific poverty lines. Applying Norwegian register data for the period 1993-2001, we find that disregarding the value of local public services and geographic cost of living differences yields a misleading picture of poverty.
Keywords: D31; H72; I30; 330; Poverty; public services; in-kind transfers; geographical cost of living differences; housing price indices; municipal-specific poverty lines